MODELLING OF THERMOELASTIC TRANSIENT CONTACT INTERACTION FOR BINARY BEARING TAKING INTO ACCOUNT CONVECTION - Igor KOLESNIKOV; Sergey DANILCHENKO; Elena KOLOSOVA; Mikhail CHEBAKOV; Alexander LYAPIN (Transport Problems, 2016)
Serviceability of metal-polymeric "dry-friction" sliding bearings depends on many parameters, including the rotational speed, friction coefficient, thermal and mechanical properties of the bearing system and, as a result, the value of contact temperature. The objective of this study is to develop a computational model for the metallic-polymer bearing, determination on the basis of this model temperature distribution, equivalent and contact stresses for elements of the bearing arrangement and selection of the optimal parameters for the bearing system to achieve thermal balance. Static problem for the combined sliding bearing with the account of heat generation due to friction has been studied in [1]; the dynamic thermoelastic problem of the shaft rotation in a single and double layer bronze bearings were investigated in [2, 3].